Ethics, fiqh and contemporary issues - Maularna Akbar shah @ U Tun Aung, U Tun Aung (2019)
It is about the ethics and fiqh for the contemporary Issues that is very much important for Muslim Ummah to know and deal with so they are updated with their understanding about latest issues.